Chandler and Grant's glaucoma - Kahook, Malik Y.; Schuman, Joel S. (SLACK Incorporated, 2021)
"Chandler and Grant's Glaucoma-one of the field's seminal texts on the medical practice and surgical management of glaucoma, now in its Sixth Edition-includes the latest updates in an area that is currently experiencing a surge of innovation. Edited by Drs. Malik Y. Kahook and Joel S. Schuman and with contributions from the late David L. Epstein and more than 80 contributors, Chandler and Grant's Glaucoma, Sixth Edition brings together the experience of world-class glaucoma experts who belong to a long line of surgeons trained using the teachings of the original authors of this classic work. Each chapter has been meticulously edited and updated from the previous edition, while maintaining the well-established historical teachings of Drs. Paul A. Chandler and W. Morton Grant. New chapters on medical therapy as well as thorough updates on novel and minimally invasive approaches for the surgical management of glaucoma have been added"--